Is Self-Sacrificial Competitive Altruism Primarily a Male Activity? - McAndrew, Francis T.; Perilloux, Carin (Evolutionary psychology, 2012)
This study explored the basis of self-sacrificial prosocial behavior in small groups. Seventy-eight undergraduates (39M, 39F) filled out a thirty-item personality scale and then participated in a “group problem-solving study” in which the monetary success of a three-person group depended upon one of its members volunteering to endure pain (a cold stressor test) and inconvenience (being soaked in a dunk tank). There were 13 groups consisting of two females and one male, and 13 groups consisting of two males and one female. Across groups, the behavior of the altruist was judged to be more costly, challenging, and important and he/she was liked better, rewarded with more money, and preferred as a future experimental partner. Groups containing two males showed more evidence of competition to become altruists than groups containing two females, and personality traits were more effective predictors of altruistic behavior in males than in females. We conclude that competition between males and “showing off” are key factors in triggering self-sacrificial altruistic behavior.